Surface Acoustic Wave Bandpass Filter Synthesis and Design - El-Diwany, Monir H. (My University, 1975)
Theory, design and fabrication of a Surface Acoustic Wave (SAW) TV-IF filter is presented in this thesis. The filter is a linear phase bandpass filter with a passband extending from 41.25 to 47.25 MHz. Optimization techniques were used for designing the filter impulse response. Conventional photolithography was used for the device fabrication. The results obtained correspond very well to the theoretical design.
Keywords: Electrical and Electronics; Electrical and Electronics